تطوير الوسيلة التعليمية فليب بوك برو لتعليم المفردات العربية بالتطبيق على التلاميذ في المدرسة - Qurrotul Aini; Muhammad Nabil Musyarrof (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
The use of learning media is essential in the learning process. The teacher needs help in choosing a proper learning media in the process of learning Arabic vocabulary. Students have difficulties memorizing vocabulary effectively and have been inattentive during the learning process. Thus, the researcher provides a solution using technology-based learning media, Flip Book Pro. It is a learning media that converts PDF files into various engaging digital book pages. The paper uses a research and development approach and uses the model of ADDIE (Analysis, Design, Development, and evaluation). The researcher conducted trials using qualitative and quantitative methods. The researcher obtained data on the effectiveness of students on the product using a qualitative approach. The researcher quantitatively analyzed the data using the Likert scale formula, data questionnaire analysis, and t-test. This paper was centered around how the process of developing flipbook pro learning media on Arabic vocabulary learning for elementary students of Baiturrohman Jember in the 2021/2022 Academic Year and finding out whether or not there is a significant effect in the effectiveness of Flipbook Pro learning media on learning Arabic vocabulary for elementary students of Baiturrohman Jember in 2021/2022 Academic Year.